Copyright : interpreting the law for libraries, archives and information services - Cornish, G. P. (Facet Publishing, 2019)
Copyright' is the standard work in its field and is indispensable for all librarians and information professionals and who are looking for solutions to their copyright problems. The book explains the provisions of the UK Copyright Act and supporting legislation in quick and easy question-and-answer form. This revised edition is fully updated to take into account of all the changes that have come into force since the 6th edition was published in 2015. All types of material that may attract copyright are considered, including: literary, dramatic and musical works artistic works sound recordings films and video broadcast databases computer programs and websites. The text is amplified by the use of practical examples to illustrate complex points and complemented by a detailed index that enables the enquirer to pinpoint topics and proposed action quickly and accurately. The appendices provide helpful lists of addresses and selected further sources of information. This book will be invaluable for all librarians, information professionals and students who are looking for solutions to their copyright problems.